UMP online shopping system - Muhammad Syamil, Sulaiman (2019)
The evolution of Internet has created a paradigm shift of the traditional way people shop. Nowadays, online shopping is one of the most convenient and best method considered for shopping. Online shopping has offered many advantages as well as disadvantages for the online shoppers. The online shoppers need to be very careful when choosing and trading online. An online shopping system that is more secured, reliable, easy to use and user friendly need to be developed in order to resolve this problem. The UMP Online Shopping System was developed to help UMP communities and the nearest community in Kuantan in purchasing and promoting products and services using the online platform. This system would improve the effectiveness and safety when trading online as the user can know the information of online merchants before meeting them in the specified safe place in UMP and Kuantan. The user of this system is UMP communities which include students, lecturers, staffs and people living in Kuantan. The UMP Online Shopping system will be develop using PHP, HTML, MySQL and JavaScript. PHP has a number of unique features and specific functions as well which will allow web developers to write dynamically generated pages quickly and easily. HTML provides building blocks to all websites, particularly text and images. JavaScript is capable of rich user experience for browser-based applications. UMP online shopping system requires database in order to store information about the products that will store pricing, description, images and details of the number of each products and services that are available. PHP and MySQL are used for communication between website and the database management systems (DBMS). The methodology used in this project development is using Rapid Application Development (RAD). This UMP Online Shopping system will be used to manage selling and buying products and any services between user and admin which required a working internet connection for it to running properly.